2021
DOI: 10.3390/ejihpe11010012
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation and Validation of the Motivated Strategies for Learning Questionnaire for Spanish Adolescents

Abstract: This work adapts and validates the scale of the motivated strategies for learning questionnaire (MSLQ), which is used to measure motivation. For this, an instrumental design was carried out with the purpose of analyzing the psychometric properties of the instrument. The sample consisted of 307 participants enrolled in compulsory secondary education. Reliability with fit indices were good in model B (proposed) with composite reliability, global reliability index, and Cronbach’s alpha. The original model (A) pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…For data collection, the adaptation to the Spanish context of the instrument Motivated Strategies for Learning Questionnaire (MSLQ) [75] was used. This tool is composed of two dimensions (1-Intrinsic Motivation (MotInt) and 2-Extrinsic Motivation (MotExt)) that articulate a total of eight items (Appendix A).…”
Section: Instrumentmentioning
confidence: 99%
“…For data collection, the adaptation to the Spanish context of the instrument Motivated Strategies for Learning Questionnaire (MSLQ) [75] was used. This tool is composed of two dimensions (1-Intrinsic Motivation (MotInt) and 2-Extrinsic Motivation (MotExt)) that articulate a total of eight items (Appendix A).…”
Section: Instrumentmentioning
confidence: 99%
“…Some instruments propose a dimensional structuring similar to the one proposed in this work ( Peña, 2014 ; Tarouco et al., 2013 ), especially in the motivational dimension developed in the MSLQ ( Segura-Robles et al., 2021 ). The interaction with technology dimension has been addressed as a fundamental aspect by authors such as Erturk and Reynolds (2020) and Estudante and Dietrich (2020) , stating that digital resources are not well designed and adapted to the metaverse and consequently, their use must be optimally analyzed.…”
Section: Discussionmentioning
confidence: 90%
“…(2013) . Furthermore, to complement these instruments, the European Digital Competence Framework was taken as a reference to incorporate the netiquette dimension and the adaptation of the Motivated Strategies for Learning Questionnaire (MSLQ) to Spanish to measure student motivation ( Segura-Robles et al., 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Gamification aims to improve internal and external motivation and make people participate in work activities. A motivation measurement study shows that the penetration of learning spaces using active methods (gamification, escape rooms, and flipped learning) and emerging technologies (e.g., robotics, augmented reality, and virtual reality) is a daily task that offers the opportunity to change the traditional teaching and learning process (Segura-Robles et al, 2021). Previous studies have also shown that intrinsic motivation can continue to affect satisfaction, and students who participate in Gamified Entrepreneurship Courses tend to show stronger interest, higher engagement, and more satisfying course experience than other students, in the context of gamification, students' influence, autonomy, creativity, and exploration ability can also be enhanced (Pozo-Sa´nchez et al, 2022;Senali et al, 2022).…”
Section: Introductionmentioning
confidence: 99%